2022
DOI: 10.1111/jcmm.17459
|View full text |Cite
|
Sign up to set email alerts
|

Protection by hydroxychloroquine prevents placental injury in obstetric antiphospholipid syndrome

Abstract: Obstetric antiphospholipid syndrome (OAPS) is mediated by antiphospholipid antibodies (aPLs, and anti‐β2 glycoprotein I antibody is the main pathogenic antibody), and recurrent abortion, preeclampsia, foetal growth restriction and other placental diseases are the main clinical characteristics of placental pathological pregnancy. It is a disease that seriously threatens the health of pregnant women. Hydroxychloroquine (HCQ) was originally used as an anti‐malaria drug and has now shown benefit in refractory OAPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
2
14
0
1
Order By: Relevance
“…Thirteen observational studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] were included in the NOS quality assessment. A summary of the evaluation result is presented in Table S4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen observational studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] were included in the NOS quality assessment. A summary of the evaluation result is presented in Table S4 .…”
Section: Resultsmentioning
confidence: 99%
“…For the comparability category, we determined pregnancy as the most important factor and diseases condition as the second. Seven studies [ 16 , 17 , 18 , 19 , 23 , 26 , 27 ] were scored as one point for not controlling for or not mentioning the second important factor, which means there may be differences in diseases condition between the two cohorts. The other six studies [ 20 , 21 , 22 , 24 , 25 , 28 ] were scored as the maximum of two points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…APS mice had lower C5a levels following treatment with HCQ, and this was observed in patients with APS as well [ 53 ]. In cultured human extravillous trophoblast cells, Liu et al demonstrated that aPL reduced the ability of normal trophoblast cells to invade, migrate and form tubules, which was partially reversed by HCQ [ 54 ]. Furthermore, in an obstetric APS mouse model, HCQ was able to reduce pregnancy complications and prevent foetal death [ 54 ].…”
Section: Hydroxychloroquine In Obstetric Apsmentioning
confidence: 99%
“…In cultured human extravillous trophoblast cells, Liu et al demonstrated that aPL reduced the ability of normal trophoblast cells to invade, migrate and form tubules, which was partially reversed by HCQ [ 54 ]. Furthermore, in an obstetric APS mouse model, HCQ was able to reduce pregnancy complications and prevent foetal death [ 54 ]. Wu et al showed that HCQ reversed the effects of aPL on primary syncytiotrophoblasts generated from cytotrophoblasts in vitro by significantly reducing IgG binding and restoring annexin A5 expression [ 55 ].…”
Section: Hydroxychloroquine In Obstetric Apsmentioning
confidence: 99%